2020
DOI: 10.32479/ijeep.9808
|View full text |Cite
|
Sign up to set email alerts
|

Do Oil Price Shocks Give Impact on Financial Performance of Manufacturing Sectors in Indonesia?

Abstract: The panel vector auto regression model is estimated using three main variables related to with profitability, financial liquidity, and financial leverage for 94 manufacturing companies from 2000 to 2017 in Indonesia. The aim is to examine the impact of oil price shocks on the ROA (profitability), CR (financial liquidity), and DER (financial leverage). The impulse reaction function of samples reveals some remarkable results. First, the response of ROA, DER, and CR appears to be consistent in many ways. Second, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…There is no doubt that whenever OG-Ps rise, the operating costs rise, and thus negative impact is witnessed in the company's financial performance especially in revenues and profitability. In many countries and in light of the inability of these companies to reflect this rise in electricity prices for consumers they endure a large portion of this surge as nonrefundable costs that consequently negatively impact financial performance (Thinagar et al, 2019;Gao et al, 2018;Wiryono et al, 2020;Aye et al, 2014;Guidi, 2009). Furthermore, this rise in oil or gas prices obligates companies to give up a larger part of their revenues to cover the purchase costs and hence negatively effects the level of profitability, liquidity and in some situations pushes these companies to cover these additional costs through borrowing in high interest rates (Mahboub and Ahmed, 2017;Nasir et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is no doubt that whenever OG-Ps rise, the operating costs rise, and thus negative impact is witnessed in the company's financial performance especially in revenues and profitability. In many countries and in light of the inability of these companies to reflect this rise in electricity prices for consumers they endure a large portion of this surge as nonrefundable costs that consequently negatively impact financial performance (Thinagar et al, 2019;Gao et al, 2018;Wiryono et al, 2020;Aye et al, 2014;Guidi, 2009). Furthermore, this rise in oil or gas prices obligates companies to give up a larger part of their revenues to cover the purchase costs and hence negatively effects the level of profitability, liquidity and in some situations pushes these companies to cover these additional costs through borrowing in high interest rates (Mahboub and Ahmed, 2017;Nasir et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The data for the sample period was analyzed using FMOLS and the outcome indicated that crude oil price exerts a positive effect on real non-crude oil price economic growth while the rate of exchange exerts a negative impact on non-crude oil price economic growth. Wiryono, Sudrajad, Prasetio, and Setiawati (2020) investigated the influence of fluctuations in crude oil price on profitability, financial liquidity and financial leverage using the sample of ninety-four manufacturing companies for the 2000-2017 periods. The outcomes indicated consistency in the case of profitability, financial liquidity and financial leverage.…”
Section: Evidence From Foreign Studiesmentioning
confidence: 99%